PENGGUNAAN VARIASI MEDIA PEMBELAJARAN IPA UNTUK MENANAMKAN KETERAMPILAN BERPIKIR TINGKAT TINGGI SISWA SEKOLAH DASAR - Rahayu, Ayu; Utaminingsih, Retno; Andini, Dinar Westri (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2020)
The purpose of this study is to describe the variation of the science learning media used to instill high order thinking skills in elementary school students. The research method used is descriptive qualitative. The study was conducted at Taman Muda Ibu Pawiyatan Yogyakarta Elementary School in the odd semester of the academic year 2018-2019. The subjects were students of class III, which amounted to 12 people. Data collection techniques are tests, observations, and interviews. Analysis of the data used in this study consisted of descriptive analysis consisting of data reduction, data presentation, and conclusion. The results showed the fact that the variation of science learning media used to instill high order thinking skills in Taman Muda Ibu Pawiyatan Yogyakarta Elementary School is the surrounding environment, concrete objects, learning videos, concept map boards, and worksheets. The media is used according to the models and methods in learning.